Effect of the reinforcement rate on goal-directed and habitual choices in a multiple schedule - Hu, Ting; Fujimaki, Shun; Kawarada, Hiroto; Kosaki, Yutaka (Frontiers in Psychology, 2025)
Voluntary behaviors can be either goal-directed, sensitive to changes in their consequences, or habitual, lacking such sensitivity. In this study, we conducted three experiments to investigate how forced-choice training influences goal-directed and habitual processes under varying reinforcement rates. In all experiments, rats received 15 training sessions on a two-component multiple schedule with two sequentially inserted levers. In Experiment 1, identical variable interval (VI) 15-s schedules were used across components for Group Rich and VI 90-s schedules for Group Lean, yielding different behavioral outcomes. Following taste aversion for one outcome, Group Lean reduced performance (i.e., goal-directed action) during an extinction test, while Group Rich did not (i.e., habit). Experiment 2 addressed differential outcome exposure by reversing training conditions: Group Rich received numerous outcomes equivalent to Group Lean in Experiment 1, and vice versa. The devaluation effects were evident in both groups. Using the same outcome across components, Experiment 3 trained rats on a multiple VI 15-s VI 90-s schedule to further clarify the role of response–outcome pairings while controlling for the total amount of outcome exposure. Although the VI 15-s component produced fewer outcomes, it led to stronger devaluation effects and residual responding. The most important finding of this study is that alternating R–O contingencies in a multiple schedule under lean reinforcement conditions consistently sustain goal-directed control even after extensive training, while richer conditions promote a shift to habitual control. These findings are discussed within a dual-system model framework in a molar context, hypothesizing that both goal-directed and habitual strength may grow more rapidly with higher reinforcement rates.